Exploring College Student Gambling Motivation - Neighbors, Clayton (2002)
The present research combined qualitative and quantitative approaches in examining gambling motives among college student gamblers. A comprehensive set of 16 gambling motives was identified by categorizing 762 open-ended reasons for gambling, provided by 184 college student gamblers. Results revealed that most college students gamble to win money, for fun, for social reasons, for excitement, or just to have something to do. Overall, the results suggest the need for an eclectic biopsychosocial approach with regard to etiology of college student gambling.